Analysis of the clinical utility of p16/Ki-67 dual staining in screening cervical lesions among women positive for high-risk HPV - Qingsong Zhang; Yunpeng Lin; Leilei Bao; Qiuyang Huang (Medicine, 2026)
Cervical cancer is closely associated with persistent infection by high-risk human papillomavirus (hrHPV). Although HPV testing offers high sensitivity, its limited specificity may result in excessive colposcopy referrals, and the triage performance of traditional liquid-based cytology (TCT) remains suboptimal among hrHPV-positive women. As a biomarker reflecting HPV-mediated cell-cycle dysregulation and aberrant proliferation, p16/Ki-67 dual staining has shown potential advantages in identifying clinically significant high-grade cervical lesions. This study aimed to evaluate the clinical utility of p16/Ki-67 dual staining in screening cervical lesions among hrHPV-positive women and to explore its role in optimizing referral strategies. Retrospectively, this single-center cohort study included 100 consecutive hrHPV-positive women who attended our clinic between October 2024 and October 2025. All participants underwent hrHPV genotyping, TCT, and p16/Ki-67 dual staining during the same visit, followed by colposcopy and histopathological assessment. Histology served as the reference standard. We evaluated the diagnostic performance of p16/Ki-67 for cervical intraepithelial neoplasia 2+ (CIN2+) lesions and compared it with TCT, HPV genotyping, and a combined triage model (hrHPV + TCT + p16/Ki-67). In addition, we simulated the screening efficiency of different colposcopy referral strategies. Among the 100 hrHPV-positive women included, 35 (35.0%) were diagnosed with CIN2+. The prevalence of HPV16 infection and the positivity rate of p16/Ki-67 dual staining were significantly higher in the CIN2+ group than in the non-CIN2+ group ( P < .01). For CIN2+ detection, p16/Ki-67 dual staining demonstrated a sensitivity of 88.6%, a specificity of 78.5%, and a negative predictive value of 93.0%. Dual-stain positivity increased progressively with cytological severity and provided meaningful triage value across atypical squamous cells of undetermined significance, low-grade squamous intraepithelial lesion, and high-grade squamous intraepithelial lesion categories. The combined triage model yielded the best diagnostic performance, with an area under the curve of 0.91. Using “dual-stain positivity or TCT ≥ atypical squamous cells of undetermined significance” as the referral threshold substantially reduced the colposcopy referral rate while maintaining a high CIN2+ detection rate. p16/Ki-67 dual staining provides high diagnostic accuracy and strong negative predictive capability for CIN2+ lesions among hrHPV-positive women. Integrating p16/Ki-67 dual staining with TCT and HPV genotyping can markedly improve screening precision and optimize colposcopy referral strategies, thereby reducing unnecessary invasive procedures and demonstrating promising clinical applicability.